LINGUISTIC STRATEGIES FOR AGE-INCLUSIVITY: ANALYSIS OF HAIKU-BASED INTERGENERATIONAL INTERACTION. (20th December 2022) - Maeda, Harumi; Wan, Emily; Matsumoto, Yoshiko
Abstract: Many studies have examined communicative and linguistic strategies helpful to the interactional inclusion of persons living with dementia (PLwD) and the promotion of an age-inclusive society (e.g., Wray, 2020; Stickle, 2020). Building on this existing body of research, our study examines question-answer sequences in conversations (Schegloff & Sacks, 1973) among younger adults and PLwD using discourse analysis methodology to illuminate effective communicative practices for facilitating more inclusive and meaningful interactions between these individuals. Findings from this methodology are complemented by analysis of post-interaction interviews. The data set for this study consists of audio-video recordings of (1) intergenerational conversations around haiku poetry in English between older adults with mild cognitive impairments (MCI) and college students, and (2) post-interaction interviews that assess participants' feelings about the experience. The data was collected as part of a larger study designed to promote social inclusion of individuals of all ages and cognitive conditions, particularly during the pandemic, via an online intergenerational haiku-making activity. The audio-video recordings were transcribed for qualitative analysis. Findings from the analysis demonstrate the effectiveness of open and emotion-focused questions (Matsumoto, Liao, Xue, 2020; Worley, 2005) in encouraging persons with MCI to express themselves on their own terms and promoting their interactional participation. By presenting the benefits of this type of question and related linguistic strategies, this study hopes to provide a basis for developing more inclusive communicative environments for people of all ages and PLwD to help improve quality of life and well-being across all stages of life.